Pemberdayaan Masyarakat Melalui Pengelolaan Sampah (Studi di Tempat Pengolahan Sampah 3R ( TPS 3R ) Kelurahan Wongkaditi Barat, Kecamatan Kota Utara, Kota Gorontalo - Muhdar, Siti Nur Aisa Binti; Igirisa, Irawaty; Sulila, Ismet (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out how to increase individual abilities, increase the ability to work in groups/team work & increase the ability to create links or social networks. The approach used is quantitative with descriptive research type. Data collection uses interviews, observation and documentation. Data analysis uses the Miles and Huberman model. The results of this research show that community empowerment through waste management at the 3R waste processing site (TPS 3R) Wongkaditi Village, North City District, Gorontalo City has been carried out quite well, namely with various efforts and cooperation carried out to increase community awareness and participation in waste management. Various parties are involved in this process, including local governments, schools, universities, environmental NGOs, local communities, and the private sector. The local government, through the Environmental Service, plays an important role in providing incentives to TPS 3R managers, providing operational support facilities, and organizing award programs for successful environmental initiatives. Apart from that, related institutions such as educational institutions, environmental NGOs and private companies are also actively involved in providing support and facilitating cooperation between communities. Collaboration includes knowledge exchange, implementation of training programs and workshops, campaigns via social media, and the establishment of cross-institutional coordination forums.